IMPROVING STUDENT ACTIVITIES, SCIENTIFIC LITERACY SKILLS, AND LEARNING OUTCOMES IN FIFTH GRADE USING THE TERAPUNG MODEL: INTEGRATING PBL, TTW, AND MIND MAPPING - Salima, Siti Radiati; Aslamiah, Aslamiah; Cinantya, Celia; Amelia, Rizky (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this study is the low level of student activity, scientific literacy skills, and learning outcomes in science content, which is attributed to one-way learning, less meaningful and abstract learning, also teaching methods that don’t adequately develop students’ scientific literacy. This study aims to analyze the improvement of activities, scientific literacy skills, and student learning outcomes using the TERAPUNG model. In this study, the subjects were VD students of SDN Semangat Dalam 2 and the CAR method with a qualitative approach was used which was carried out 4 meetings. The instruments used were multiple-choice questions and observation sheets. This study shows that students' activities significantly improved, achieving almost entirely active criteria. Students' scientific literacy skills also saw a substantial increase in the high category, while student learning outcomes approached almost entirely complete criteria. Therefore, it can be concluded that the use of the TERAPUNG model is effective in improving student activities, scientific literacy skills, and learning outcomes.